The Impact of Bank-Specific and Macroeconomic Variables on Commercial Banks Profitability in Nepal (Patan Pragya, 2022)
This study aims to evaluate the impact of bank-specific and macroeconomic variables on commercial banks' profitability in Nepal. The study uses panel data of twenty-four commercial banks from 2011/12 to 2019/20. The study finds that bank-specific variables such as capital adequacy ratio, non-performing loan, and Cost of funds negatively affect banks' profitability (ROA and ROE). In contrast, interest rate spread, total investment to total asset, and net interest income to total asset have a positive effect. Regarding macroeconomic variables, gross domestic product (GDP)positively impacts banks' performance, while inflation (INF) has a negative impact. The study concludes that the macroeconomic variable INF is the primary determinant of banks' profitability because it also adversely influences GDP.